2022
DOI: 10.5306/wjco.v13.i7.609
|View full text |Cite
|
Sign up to set email alerts
|

Decreased incidence of febrile neutropenia in Michigan following masking and social distancing orders for the COVID-19 pandemic: A population based cohort study

Abstract: BACKGROUND It has been theorized that 75%-80% of febrile neutropenia (FN) is caused by endogenous pathogens, while up to 20% of cases are thought to be caused by a viral infection. It is unknown if precautions such as masking and social distancing reduce the risk of FN in susceptible populations. AIM To determine whether coronavirus disease 2019 (COVID-19) infection mitigation efforts, namely masking and social distancing, were associated with a reduction in the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…At the beginning of our study, there was no report on the relationship between FN and COVID 19 outbreak, however, several recent research results have been reported. The result of each study though similar in some aspect, differed as highlighted in table 5 (19)(20)(21)(22)(23). Nessle et al reported only a reduced incidence of upper respiratory infection associated FN, and not overall FN episodes among pediatric patients with cancer during post-COVID 19 era (19).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…At the beginning of our study, there was no report on the relationship between FN and COVID 19 outbreak, however, several recent research results have been reported. The result of each study though similar in some aspect, differed as highlighted in table 5 (19)(20)(21)(22)(23). Nessle et al reported only a reduced incidence of upper respiratory infection associated FN, and not overall FN episodes among pediatric patients with cancer during post-COVID 19 era (19).…”
Section: Discussionmentioning
confidence: 94%
“…Three other retrospective studies showed a reduction in the overall FN incidence after COVID 19 outbreak in relatively larger dataset. However, these data were derived from heterogeneous disease groups with different tumor types, chemotherapy regimen, patient's characteristics (20,21,23). Furthermore, Baracy et al reported an unexpected nding that FN episodes were reduced only in patients with hematologic malignancies (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation